The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10554-011-9934-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new methodology for the assessment of 3D myocardial strain from volumetric ultrasound with 2D speckle tracking

Abstract: An alternative approach to extract 3D myocardial strain based on elastic registration of the ultrasound images (3DSE) was developed by our lab. The aim of the present study was to test its clinical performance by comparing strain values obtained by 3DSE with the ones obtained with 2D speckle tracking (2DST). Standard 2D B-mode and volumetric datasets were acquired in 12 patients with coronary heart disease (CHD) and in 12 control subjects. Longitudinal (ε(LL)), circumferential (ε(CC)) and radial (ε(RR)) strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Our study is in agreement with previous studies showing that 3D STE provides global and regional 30,32,33 longitudinal and circumferential strain values that are comparable with the ones obtained on 2D STE. Both 2D STE and 3D STE were more sensitive to detect subtle myocardial changes in LV function compared with conventional indices.…”
Section: Three-dimensional Strain Versus 2d Strainsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study is in agreement with previous studies showing that 3D STE provides global and regional 30,32,33 longitudinal and circumferential strain values that are comparable with the ones obtained on 2D STE. Both 2D STE and 3D STE were more sensitive to detect subtle myocardial changes in LV function compared with conventional indices.…”
Section: Three-dimensional Strain Versus 2d Strainsupporting
confidence: 93%
“…However, this advantage is achieved at the expense of a lower volume rate, which might alter the correlations with measurements obtained by 2D STE. 33 …”
Section: Three-dimensional Strain Versus 2d Strainmentioning
confidence: 99%
“…Mean errors were 11.5%, -2.9% and -5.0% for RR , LL and CC respectively. These observations are consistent with a previous clinical study in which we compared the 3D segmental strain estimates against those obtained with 2D techniques (r=0.63 for LL , r=0.41 for CC and no significant correlation for RR ) [10]. Myronenko et al developed a comparable registration method, but they only reported sonomicrometry correlations for global twist and results for strain measurements were lumped for all directions [5].…”
Section: Discussionsupporting
confidence: 89%
“…Several studies compared 2D and 3D US wall motion [7], global deformation [8], [9] and strain values [10], [11]. These studies compared the consistency of results, the computation time and the number of segments analyzed by 2D and 3D speckle tracking.…”
Section: A Validation Of 3d Us Strain Algorithmsmentioning
confidence: 99%